The CREATOUR® project as a learning laboratory: Reflections of a research team - Gato, M. A.; Tomaz, E.; Cruz, A. R.; Perestrelo, M.; Costa, P. (Creative tourism regenerative development and destination resilience: Conference programme and presentation abstracts, 2022)
Beyond a research project, CREATOUR® [mainland Portugal] was a true laboratory of methodological experiences and joint learnings that challenged the necessity and the usefulness of developing evaluative reflection afterwards. This paper intends to provide an overview of some of the work done by the research team of DINAMIA’CET_Iscte in the CREATOUR® project and to present some reflections on this action-research experience. Based on this work are several methodologies used throughout a collaborative process with promoters of the 40 creative tourism pilot initiatives developed under CREATOUR and that allowed to identify an array of challenges and opportunities which the future national network of creative tourism may face, as well as a first reflection on the possible impacts arising from these activities. Already with some temporal distance and after a difficult pandemic, these reflections seek to provide a more comprehensive and complementary glance at the results achieved, in particular in relation to the perspectives of sustainability and resilience of a future network of creative tourism, as well as the impacts of this niche offer in the respective territories.